2010
DOI: 10.1007/s12548-011-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for temporomandibular disorders: a retrospective survey from 300 consecutive patients seeking care for TMD in a French dental school

Abstract: Purpose: The purpose of this study was to observe the prevalence of the different diagnostic groups of TMD disorders (articular, muscular, and associated disorders) and the prevalence of the different TMD risk factors from a population of patients seeking specialized care in the TMD clinic at a public dental school.Materials and methods: Data were collected from the retrospective analysis of archival records of 500 consecutive new patients who attended the TMD clinic at the Dental School of Lyon, France, over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
1
4
0
9
Order By: Relevance
“…On the other hand, a study by Robinand Chiomentowas done in 2010 in which they identified the three most prevalent risk factors for TMD to be, oral parafunctions, traumatic factors, and psychological factors. (15) Another finding was that there was no correlation between TMD and neck/cervical pain. The relation between cervical/neck pain and TMD has been observed by many authors in the literature such as Visscher et alshowed that chronic cranio mandibular pain patients more often suffer from cervical spinal pain than controls.…”
Section: Result:-mentioning
confidence: 99%
“…On the other hand, a study by Robinand Chiomentowas done in 2010 in which they identified the three most prevalent risk factors for TMD to be, oral parafunctions, traumatic factors, and psychological factors. (15) Another finding was that there was no correlation between TMD and neck/cervical pain. The relation between cervical/neck pain and TMD has been observed by many authors in the literature such as Visscher et alshowed that chronic cranio mandibular pain patients more often suffer from cervical spinal pain than controls.…”
Section: Result:-mentioning
confidence: 99%
“…La Disfunción Craneomandibular (DCM) o trastornos témporomandibulares son un conjunto de alteraciones funcionales del aparato estomatognático 1 , que afectan a las articulaciones témporomandibulares (ATMs), a los músculos masticatorios, y estructuras asociadas de cabeza y cuello 2,3 . El aparato estomatognático es complejo y requiere un conocimiento riguroso de la anatomía y fisiología de sus componentes estructurales.…”
Section: Introductionunclassified
“…Example of initiating factor is trauma or adverse loading to TMJ, while perpetuating factors may include behavioral, social, emotional and cognitive factors. Based on a retrospective study carried out in a TMD clinic in France, the two most prevalent factors were toothclenching (77% of patients) and psychological stress (59.3%), followed by antecedents of wisdom tooth extraction (34.3%) (8). In line with the understanding that third molar removal is a risk factor for TMD, Deangelis has highlighted the importance of preoperative evaluation of the TMJ apparatus prior to carrying out the surgery (9,10).…”
mentioning
confidence: 99%